PERAN MEDIA SOSIAL DAN KONTEN DIGITAL DALAM MENYEBARKAN BAHASA INDONESIA KE PUBLIK GLOBAL - Angga Hermawan; Natalia Purba; Nur Nabillah Hardiani; Yudi Albertus Tamba; Samelino Aritonang; Nikolas Marulitua Gultom (JOURNAL SAINS STUDENT RESEARCH, 2025)
The article examines the role of social media and digital content in promoting the indonesian language to a global audience. Social media, as an essential element of the digital era, plays a dual role: on the one hand, it expands the reach of indonesian worldwide, while on the other hand, it encourages linguistik shifts through the use of slang, abbreviation, and foreign language mixtures. This study applies a library research method by reviewing literature related to language development, social media, and globalization. The finding indicate that social media serves as an effectives medium to introduce indonesian to young generations and foreign learnes, as well as a tool for cultural preservation. Nevertheless, digital language literacy is required to ensure that indonesian remains used correctly and in accordance with formal standards.